Synchronous detection of bolts looseness position and degree based on fusing electro-mechanical impedance. (15th July 2022) - Wang, Lintao; Yuan, Bo; Xu, Zhenbang; Sun, Qingchao
Highlights: The relationship between the excitation frequency and detection range of PZT was explored. The EMI measured under multiple frequency ranges were fused. Impedance shift was used as damage feature. Feasibility was verified in the flange connection structure. Abstract: Looseness is the most common form of failure in bolt connections, which can cause safety accidents by reducing the rigidity of the structural connection, and the detection of bolt looseness is vital to maintain the health of the structure. However, due to the limitations of existing methods, it is difficult to detect the position of loose bolt and degree of looseness synchronously. In this study, an Electro-mechanical impedance (EMI) detection method based on fusing multi-frequency ranges was proposed. Firstly, the feasibility of bolt looseness detection based on EMI technology was analyzed through theoretical deduction; secondly, the qualitative relationship between excitation frequency and detection range was explored through finite element simulation, which provides a basis for the proposed fusing multi-frequency ranges method, and the conclusion was verified in four-bolted flange structure; finally, a detection method for bolt looseness was proposed, which uses the impedance shift as the damage index, and detect the position of loose bolt and degree of looseness synchronously by fusing EMI in multiple frequency ranges. The verification results show that the proposed method can identify the loosening status of bolts in the flange structure with high accuracy.